Kepuasan Pengguna Layanan Laboratorium Pendidikan Keperawatan - Juniari, Ni Made; Suardani, Ni Luh Ketut (Jurnal Gema Keperawatan, 2023)
Laboratories are supporting units in higher education institutions. Therefore, it needs to be supported by good laboratory management so that the implementation of activities can run optimally. The educational laboratory at the Denpasar Health Polytechnic Nursing Department serves more than 800 users every year. So it is deemed necessary to assess the satisfaction of users of laboratory services and find out what things are the priorities to be improved, to achieve optimal service. The purpose of this study is to determine the level of satisfaction with the service quality method and analysis of the importance of performance that needs to be improved to achieve a laboratory management system that can provide satisfactory service. This research is quantitative descriptive research. The number of samples in this study was 455 respondents. Data on user satisfaction of laboratory services was collected using a questionnaire. The analysis technique begins with an analysis of the gap between user perceptions and expectations, followed by an analysis with the Importance Performance Analysis (IPA) matrix. The research results show that the gap for all attributes is negative, which means that expectations are higher than perceived perceptions. The tangible dimension produces a gap of -0,55 and a service quality value of 0.89 from the division of perceptions with expectations so that it is lowest ranked  and is the dimension that has the biggest gap among all dimensions. The results of the IPA analysis show that there are still 6 attributes in quadrant I, so it is necessary to make improvements to these six attributes.